The Concept and Content of the Tenth Cause Methodology of Four Aplications in Decimals Fraction - Tashpulotova Dilfuza Burxonovna (International Journal on Economics, Finance and Sustainable Development, 2021)
The article describes the teaching methods and theories that can be used to increase the effectiveness of education in secondary schools, to teach decimals.